Prevalence of overweight and obesity among nurses in Bahrain: A cross‐sectional study - Husain Nasaif; Maryam Alaradi; Ridha Hammam (Wiley, 2024)
Abstract Aim This study aims to estimate the prevalence of overweight and obesity among nurses in Bahrain. Design A cross‐sectional design. Methods A secondary data from a convenience sample of 550 nurses working in three hospitals in the Kingdom of Bahrain. The prevalence of overweight and obesity was determined by calculating the percentages of BMI using the World Health Organization classification. Results Most participants were females (n = 488, 89.1%), ages 31 to 40 (n = 239, 43.8%). The mean BMI was 26.9 (±4.4). The prevalence of overweight and obesity was 43.2% and 21.4%, respectively. The prevalence of overweight and obesity is associated with nationality and shift work. We used BMI to estimate the prevalence of overweight and obesity. However, BMI does not consider muscle mass, bone density, body composition, and racial and sex differences. Therefore, in future studies, body fat proportion and muscle mass need to be measured to estimate the prevalence and predict risks.